How does independent director affect tunneling?—Evidence from social networks - Cheng, Hanxiu; Wang, Jie; Xing, Mu (Frontiers in Psychology, 2022)
Given the influence of controlling shareholders on the company, it is important to analyze how independent directors can protect minority shareholders' interests using the information and resources obtained from social networks. This paper studies the impact of director networks on controlling shareholders' tunneling behavior in China over the period 2002-2020. Using social network analysis, this paper finds that controlling shareholders' appropriation to minority shareholders is mitigated in companies with well-connected independent directors. These results remain consistent after a series of robustness and endogeneity tests. This study also reveals that internal controls play a mediating role between director networks and tunneling behavior. In addition, the study indicates that the restraining effect of director networks on controlling shareholders' tunneling behavior is more pronounced in companies with weaker audit monitoring and poorer transparency. In conclusion, the results reveal that well-connected independent directors play an important role in protecting minority shareholders' interests.